Synthesis of Copper Ferrite Nanoparticle using Co-Precipitation Method - Rushmittha, J.J.; Radhika, S.; Padma, C.M. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Ferrite based magnetic nanoparticles have generated unique identity among researchers because of its wide applications from biomedical to industrial range. Copper ferrite nanoparticles are one among those with great potential in the application of technological field. CuFe2O4 NPs were synthesised using chemical co-precipitation method. The synthesised sample were studied using powder X-ray diffraction (XRD). Scherrer analysis and WH-Plot were used to study the size and lattice strain of the synthesised sample. The Crystallite size of the sample were calculated as 16.79nm in range